47 Anticoagulation variability as a predictor of bleeding in patients with mechanical heart valves. (25th October 2019) - Obeid, Fadi; Obeid, Fadi; Sirryeh, Reem; Refaeis, Samia; Farah, Iyad; Shnaikat, Samir; Mahmud, Azra; Alsaileek, Ahmed
Abstract : Background: Patients with mechanical heart valves require life-long anticoagulation with warfarin. Variability of anticoagulation is a major concern in such patients. Previously, we found that mechanical heart valve patients spent only 66% of their time within the therapeutic range (TTR). However, there is currently little data relating quality of anticoagulation to bleeding risk in patients with mechanical heart valve prostheses. Methods: This was a cross-sectional study of patients attending a Nurse-Led Heart Valve Anticoagulation Clinic. Data analyzed included patient demographics, comorbidities, and concurrent drug therapy to calculate HAS-BLED and ATRIA scores. International normalized ratio (INR) values were used to calculate time spent in the therapeutic range (TTR) by the Rosendaal Method. The relationship between variables was analyzed using linear correlation (Spearman Rho) and logistic regression as deemed appropriate. Data were analyzed using SPSS (SPSS for Windows), with p<0.05 considered significant. Results: The study cohort consisted of 260 patients with a mean age of 54±15 years. The mean TTR was 66+16%. 27 (10%) patients had HAS-BLED scores of more than 3 (high risk). Bleeding (cerebral, gastrointestinal, or hemoglobin <100 g/L) occurred in 32 (12.3%) patients; 12 (37.5%) of these patients had a HAS-BLED score of more than 3 (p=0.0001). TTR was not different between patients with or without bleeding (64.1+19.4% versus 66.3+16.1%). On the other hand, mean HAS-BLED and ATRIA scores were significantly higher in patients who had bleeding. Using multivariate analysis, ATRIA score followed by HAS- BLED score was the best predictor of bleeding. Age, sex, and TTR as a measure of INR variability did not show a significant difference between the two groups. Conclusion: Similar to previous reports of patients with atrial fibrillation, ATRIA and HAS-BLED scores were the best predictors of bleeding in our cohort of patients with mechanical heart valves, with no independent contribution of TTR to estimation of bleeding risk.